De novo acute myeloid leukemia with 20–29% blasts is less aggressive than acute myeloid leukemia with ≥30% blasts in older adults: a Bone Marrow Pathology Group study. Issue 11 (31st July 2014) - Hasserjian, Robert Paul; Campigotto, Federico; Klepeis, Veronica; Fu, Bin; Wang, Sa A.; Bueso‐Ramos, Carlos; Cascio, Michael Joseph; Rogers, Heesun Joyce; Hsi, Eric Darryl; Soderquist, Craig; Bagg, Adam; Yan, Jiong; et al.
<x xml:space="preserve">Abstract</x> It is controversial whether acute myeloid leukemia (AML) patients with 20–29% bone marrow (BM) blasts, formerly referred to as refractory anemia with excess blasts in transformation (RAEBT), should be considered AML or myelodysplastic syndrome (MDS) for the purposes of treatment and prognostication. We retrospectively studied 571 de novo AML in patients aged >50 years, including 142 RAEBT and 429 with ≥30% blasts (AML30), as well as 151 patients with 10–19% BM blasts (RAEB2). RAEBT patients were older and had lower white blood count, but higher hemoglobin, platelet count, and karyotype risk scores compared to AML30, while these features were similar to RAEB2. FLT3 and NPM1 mutations and monocytic morphology occurred more commonly in AML30 than in RAEBT. RAEBT patients were treated less often with induction therapy than AML30, whereas allogeneic stem cell transplant frequency was similar. The median and 4‐year OS of RAEBT patients were longer than those of AML30 patients (20.5 vs 12.0 months and 28.6% vs 20.4%, respectively, P = 0.003); this difference in OS was manifested in patients in the intermediate UKMRC karyotype risk group, whereas OS of RAEBT patients and AML30 patients in the adverse karyotype risk group were not significantly different. Multivariable analysis showed that RAEBT (P < 0.0001), hemoglobin (P = 0.005), UKMRC karyotype risk group (P = 0.002), normal BM karyotype (P = 0.004), treatment with induction therapy (P < 0.0001), and stem cell transplant (P < 0.0001) were associated with longer OS. Our findings favor considering de novo RAEBT as a favorable prognostic subgroup of AML. Am. J. Hematol. 89:E193–E199, 2014. © 2014 Wiley Periodicals, Inc.